PRINSIP KEADILAN DALAM MUAMALAH BERDASARKAN PERSPEKTIF AL-QUR’AN - Dini Cahyani Nasution; Ferizal; Dwi Silvia Ningsih; Ika Amelia Putri; Lidya Rosnoviana; Muhammad Fauzan Ramadhan; Rahma Intan Nuraini; Sherina; Vina Widia Afriani (Al-Insyirah: Jurnal Pendidikan dan Konseling Islam, 2026)
This study aims to analyze the principle of justice in muamalah based on the perspective of the Qur'an. Justice is a fundamental value in Islam that must be applied in every aspect of economic interaction. Through the approach of interpretation and fiqh, this study examines various verses related to muamalah and the principles of justice contained therein. The results of the study show that the Qur'an provides clear guidelines regarding the importance of justice, prohibitions on detrimental practices such as usury, fraud, and injustice in transactions. In addition, this study emphasizes that the application of the principle of justice will not only create a fairer economic system, but also improve the welfare of society as a whole. Thus, it is hoped that this study can contribute to strengthening the practice of muamalah that is fair and in accordance with Islamic teachings, in order to create a more prosperous and harmonious life in society.